Prevalensi dan identifikasi cemaran bakteri patogen staphylococcus aureus pada ayam krispy Daerah Amplas Kota Medan menggunakan rabbit coagulase plasma with EDTA - Rahayu, Yayuk Putri; Nasution, Haris Munandar; Supiyani, Supiyani (Journal of Pharmaceutical and Sciences, 2024)
Staphyococcus aureus bacteria is one of the bacteria that contaminates crispy chicken meat and can cause Extraordinary Events or Kejadian Luar Biasa (KLB) in Indonesia as a cause of diarrhea. This is due to lack of hygiene in processing, storing and serving crispy chicken. Poisoning can occur due to food contamination by S. aureus enterotoxin. The aim of the research was to analyze the prevalence and identify the presence of S. aureus bacteria found in crispy chicken meat in the Amplas area of Medan city using Rabbit Coagulase Plasma with EDTA. Method for identifying S. aureus using BPA (Baird Parker Agar Base) and Egg Yolk media. Specific identification testing using Gram staining, catalase test, and coagulase test using Rabbit Coagulase Plasma with EDTA. The value of S. aureus bacterial contamination using the TPC (Total Plate Count) method and analysis of the prevalence of S. aureus contamination. The results of research on roadside cart krispy chickens were found to be positive for S. aureus with characteristics of Gram positive, positive coagulase and positive catalase as well as contamination values above 1X102 CFU/ml exceeding the threshold so they do not meet SNI standards. Meanwhile, the local fast food crispy chicken value for the presence of S. aureus bacteria does not exceed the threshold of 1X102 CFU/ml so it meets SNI standards. The prevalence value of S. aureus contamination in roadside cart krispy chicken was 75.0% and local fast food was 8.3%.